Waste collection route optimisation model for linking cost saving and emission reduction to achieve sustainable development goals - Hannan M.A.; Begum R.A.; Al-Shetwi A.Q.; Ker P.J.; Al Mamun M.A.; Hussain A.; Basri H.; Mahlia T.M.I. (Elsevier Ltd, 2023)
Budget control; Cost effectiveness; Cost reduction; Efficiency; Emission control; Integer programming; Planning; Solid wastes; Sustainable development; Carbon emission reductions; Collection efficiency; Mixed integer linear programming model; Optimisation models; Route optimisation; Solid waste collection; Transportation system; Waste management systems; Waste management